Pengembangan Moduseksi untuk Anak Retardasi Mental sebagai Upaya Preventif Pelecehan Seksual - Machmudah Machmudah; Sunanto Sunanto; Nanang Rokhman Saleh (Universitas Muhammadiyah Jember, 2021)
Like normal children in general, sexual education should be given from an early age also to children with special needs, especially children with mental retardation. Mental retardation or intellectual disability is a pathological condition in the brain from birth that shows limitations in intellectual function and other adaptive functions, including mental function, communication skills, self-care and social skills. The purpose of this study was to determine the effectiveness of moderation psychoeducation on increasing knowledge of sex education in mentally retarded children. This study used quantitative research methods with a one-group pretest-posttest design. The subjects used in the study werestudents and parents of students at SLB AKW Surabaya aged under 8 years with a total of 21 subjects. This study was analyzed using the Wilcoxon sing-ranked test to measure the effect of sex psychoeducation. The p-value = 0.000 (p 0.01), indicates that the knowledge of parents and mentally retarded children about sexual harassment has increased after being given a moderation psychoeducation intervention.